حديث «من بدل دينه فاقتلوه» إشكاليته وحلوله بين المتقدمين والمتأخرين (Problem and Solution on the Ḥadīth "Whoever changes his religion, kill him": A Study of the Approaches of Traditional and Contemporary Scholars) - الخيرآبادي محمد أبو الليث; بنت أحمد نظرة; بنت فتاح ياسين روضة الفردوس; مرزوقي زنيدة محمد (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
الملخّص لقد حاول البحث الوقوف على الفهم الأنسب لمعنى قوله صلى الله عليه وسلم: «من بدل دينه فاقتلوه». وقد تبيَّن من خلال استعراض آراء العلماء القدامى والمعاصرين في فهمهم أو تعاملهم مع هذا الحديث والأحاديث الدائرة في فلكه أنه قد ظهرت عدة فهوم أو تأويلات لهذا الحديث، من القول بقتل المرتد حدًّا على الفور، ثم باستتابته لفترة محدودة، ثم استتابته أبداً، ثم الإيماء فالقول بقتله تعزيراً، والقول بعدم تجريمه أصلاً. فهكذا يمكن القول بأن تأويل هذا الحديث قد شهد نوعاً من التطور في اتجاه العدول عن قتل المرتد. ولقد لاحظ الباحثون وجود نوع من الارتباط بين هذه الأطوار والوضع السياسي والثقافي والاجتماعي السائد في الدولة الإسلامية وبين المسلمين في وقت ذلك الطور. ومن جهة أخرى فقد أشار الباحثون إلى أن الحديث لم يكن فيه أي إشكال في عهد الصحابة والتابعين وتابعيهم، بل لم يظهر إشكال تعارض حديث البحث مع القرآن إلا عند بعض المعاصرين، حينما راجت فكرة الحرية وحرية المعتقد بالذات. والذي تبيَّن للباحثين بعد استعراض أدلة كل الاتجاهات ثم مناقشتها وتحليلها وتقييمها هو القول بوجوب معاقبة المرتد بالقتل بعد الاستتابة وجوباً، مع ترك فترة الاستتابة مهما طالت أو قصرت للحاكم، وحسب ما يراه مناسباً للظرف السياسي والثقافي والاجتماعي للدولة الإسلامية، محقِّقاً للمصلحة البيِّنة والحقيقية، ومقدِّراً بحسب الضرورة القائمة والحاجة الداعية، كما لا بد من الموازنة بين المصلحة في عدم قتل المرتد على الفور، وسد الذريعة أمام كل من تسوِّل له نفسه الردة عن الإسلام عن طريق قتل المرتدين ليكونوا عبرةً لغيرهم. وإلى جانب هذا يدعو الباحثون إلى ضرورة التفريق بين المرتدين، وأن التفرقة في التعامل معهم يجب أن تراعى فيها درجة خطورتهم ومدى تأثيرهم على غيرهم من عدمها. كما يتعين مراعاة حالة الدولة الإسلامية والمسلمين من قوة وضعف. الكلمات المفتاحية: قتل المرتد، حد، تعزير، استتابة المرتد. Abstract This study seeks to reach the most appropriate understanding of the ḥadīth "whoever changes his religion, kill him". Having surveyed the views of traditional and contemporary scholars vis-a-vis their interpretation of this hadith and other similar Prophetic traditions, it is evident that there are various concerns and interpretations, ranging from killing the apostate instantly, killing after asking for repentance within a limited period, to killing after asking for repentance at any time. Afterwards, some scholars argued this hadith was indirect reference for giving deterrent punishment while others viewed that one cannot be incriminated at all on the course of changing his religion. Thus, it can be presumed that the interpretation of this ḥadīth has witnessed a kind of evolution to the direction of abstention from the killing of an apostate. This study notes the existence of some sort of correlation between these stages of evolution and the political, cultural and social situation prevailing in the Islamic state and among Muslims at the time of that respective phase. On the other hand, this study points out that there was no problem in the hadith during the era of the Companions and the followers of the Ṣaḥābah and their followers. Rather, no conflict was reported between this ḥadīth and the Qur’an except with some modern scholars when the idea of freedom and freedom of faith gained momentum. What is evident after a thorough analysis of maximum proofs of all variant opinions and their assessment is the assertion of wujub upon the execution of the apostate after his atonement; although the nature of interval allowed for the atonement remains open to be decided by ruler of the state. The ruler is further authorized to contemplate on the socio-political and cultural scenario of the Islamic country and free to assess them, in a way which is conducive to ensure the realization of social benefit and to appreciate the pressing need of the retribution. It is, however, incumbent upon the ruler to compare the situation of capital punishment with another scenario of delaying it, which may be helpful to achieve any benefit. Likewise, he is also enjoined to block all the possible means failure of which may lead to the emergence of other apostates in the future, so as to facilitate them to draw lessons from the previous executions. Besides this, the researchers would like to suggest that there is a necessity of segregation between each and every apostate, so that it could reduce the intensity of peril caused by them towards others and the potential influence they will inflict upon the Islamic state, in general, and the other susceptible personalities, in particular. Keywords: Apostate, Articulated Punishment, General Punishment, Repentance Option.